Urbanisation, land use, land degradation, and environment - Öztürk, Münir A. (Münir Ahmet); Mermut, A.R. (Ahmet R.); Celik, Ali (Daya Pub. House, 2011)
Papers presented at the International Workshop on "Urbanization, Land Use, Land Degradation and Environment", jointly organized by Pamukkale University, Turkish Scientific and Technical Research Organization and the Center for Science and Technology of the Non-Aligned and Other Developing Countries during 28th September-1st October 2009 in Denizli, Turkey.